Urine extracellular vesicle miRNA changes induced by Vicadrostat with/without Empagliflozin in patients with chronic kidney disease - Delic, Denis; Gashaw, Isabella; Duran-Fernandez, Ileana; Cronin, Lisa; Hauske, Sibylle J.; Rossing, Peter; Tuttle, Katherine R. (International journal of molecular sciences, 2025)
Vicadrostat, a selective aldosterone synthase inhibitor, reduced albuminuria with concurrent renin-angiotensin system inhibition and empagliflozin, suggesting additive efficacy for chronic kidney disease (CKD) treatment. Specific urinary extracellular vesicle microRNAs (uEV miRNAs) may reflect key mechanisms of kidney injury. We investigated how vicadrostat alone or with empagliflozin affected uEV miRNA expression in study participants. Small RNA sequencing was conducted on uEV miRNAs from 435 participants with CKD who completed 14 weeks treatment in the phase II trial of vicadrostat given with or without empagliflozin. Differentially expressed uEV miRNAs in participants with ≥30% UACR (urine albumin-creatinine ratio) reduction treated with 10 or 20 mg vicadrostat were pooled and evaluated with or without empagliflozin. Changes in miRNA-142-5p correlated significantly with changes in UACR in participants treated with vicadrostat alone, whereas changes in expression of eight additional uEV miRNAs (miR-192-5p, miR-194-5p, miR-6882-5p, miR-27a-5p, miR-381-3p, miR-192-3p, miR-513a-5p, and miR-199b-3p) correlated with ≥30% UACR improvements in patients treated with vicadrostat plus empagliflozin. Cellular deconvolution revealed that these miRNAs were expressed in various kidney cell types. Vicadrostat plus empagliflozin altered uEV miRNAs involved in immunomodulatory and fibrotic pathways irrespective of participant diabetes status. Regulation of miRNAs may provide insights into synergistic mechanisms of vicadrostat and empagliflozin in CKD treatment.
Veröffentlicht: 7. November 2025
Gesehen am 28.01.2026